Exploiting Sino-US Geostrategic Competition: The View from Seoul and Singapore. Issue 3 (3rd July 2018) - Park, Jae Jeok; Tan, Erwin
ABSTRACT: The mainstream literature on weak status quo states' diplomacy tends to identify their regional security roles in terms of dealing with non-traditional security issues. This article argues that such a limited approach is not sufficient to explain the current security dynamics in the Asia-Pacific. This article reviews the literature on weak status quo states' influence on regional order. It then identifies a security environment in which they are more likely to exert some impact on maintaining and building a regional order. After contextualising these discussions in the Asia-Pacific setting, the article examines the experience of South Korea and Singapore as secondary powers in the East Asian region. Although both countries enjoy high levels of security cooperation with the US, both have also been able to exercise a certain amount of influence in advancing their own geostrategic interests amidst the growing Sino-US geostrategic competition. Yet their exploitation of Sino-US geostrategic competition is neither a simple balancing strategy against China nor a simple bandwagoning with the US, since both South Korea and Singapore have been increasing bilateral and multilateral security cooperation with China.